Involving Undergraduates in Research To Encourage Them To Undertake Ph.D. Study in Economics - Ehrenberg, Ronald G (American Economic Review, 2005)
Involving Undergraduates in Research To Encourage Them To Undertake Ph.D. Study in Economics by Ronald G. Ehrenberg. Published in volume 95, issue 2, pages 184-188 of American Economic Review, May 2005